ANALISIS STRATEGI BAURAN PEMASARAN SERTA PENGARUHNYA TERHADAP MINAT DAN KEPUTUSAN PEMBELIAN PRODUK KERTAS PADAPT. RIAU ANDALAN PULP AND PAPER (PT.RAPP) PANGKALAN KERINCI RIAU (Jurnal Tepak Manajemen Bisnis, 2014)
This study aims to examine and analyze the effect of marketing mix is the product, price, and channeldistribution of the paper purchase decision through buying interest either simultaneously or partially in PT.Riau Andalan Pulp and Paper Pangkalan Kerinci Riau . The data used in this study are primary and secondarydata. For primary data is data obtained from questionnaires distributed and interview. Secondary data derivedfrom data owned by the company. Sampling in this study using census method in order to get a sample of 106respondents. The analytical method used was path analysis or path analysis.From the results of analyzes obtained that the variable product, price, distribution channels, and buying interesthas the simultaneous effect of the 37.9 % variable purchase decision. And the three variables of the marketingmix of product, price, and distribution channels that have the greatest influence on purchasing decisions is thedistribution channel with a value of 0.357. The results showed that the variable product, price, and distributionchannels enough to affect the purchasing decisions through buying interest. Therefore, reliable distribution,competitive pricing, and product development must be pursued so that the company will gain a competitiveposition in the market.Keywords: Marketing Mix, Buying Interest, and Purchasing Decision